2019
DOI: 10.1016/s0140-6736(18)33212-4
|View full text |Cite
|
Sign up to set email alerts
|

Placental growth factor testing to assess women with suspected pre-eclampsia: a multicentre, pragmatic, stepped-wedge cluster-randomised controlled trial

Abstract: Summary Background Previous prospective cohort studies have shown that angiogenic factors have a high diagnostic accuracy in women with suspected pre-eclampsia, but we remain uncertain of the effectiveness of these tests in a real-world setting. We therefore aimed to determine whether knowledge of the circulating concentration of placental growth factor (PlGF), an angiogenic factor, integrated with a clinical management algorithm, decreased the time for clinicians to make a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
191
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 25 publications
1
191
1
1
Order By: Relevance
“…With a larger placenta comes higher levels of these circulating angiogenic factors, and studies have shown increased risk of preeclampsia with each for each 2‐fold elevation in sFlt‐1 . Prediction of preeclampsia using these angiogenic factors is topical at present; however, their utility in aiding diagnoses of preeclampsia in multiple pregnancy warrants further research …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a larger placenta comes higher levels of these circulating angiogenic factors, and studies have shown increased risk of preeclampsia with each for each 2‐fold elevation in sFlt‐1 . Prediction of preeclampsia using these angiogenic factors is topical at present; however, their utility in aiding diagnoses of preeclampsia in multiple pregnancy warrants further research …”
Section: Discussionmentioning
confidence: 99%
“…24 Prediction of preeclampsia using these angiogenic factors is topical at present; however, their utility in aiding diagnoses of preeclampsia in multiple pregnancy warrants further research. 25,26 Maternal age >40 years, nulliparity and conception through use of a donor oocyte are all well-established risk factors for HDP in both singleton and multiple pregnancies. 27 Over the last number of decades, use of ART has increased and pregnancy through use of a donor oocyte is now common.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with standard practice, there was a reduction seen in the median time to diagnosis of preeclampsia from 4.1 to 1.9 days (time ratio 0.36, 95% CI 0.15-0.87) with a concurrent reduction in severe maternal adverse outcomes (5.4-3.8%, adjusted odds ratio 0.32, 95% CI 0.11-0.96). 12 Of women who tested "normal" for PlGF (>100 pg/mL) in the PARROT trial, 10.9% went on to receive a diagnosis of preeclampsia in the pregnancy. In 2016, there was one small study of 100 women published which looked at repeated PlGF measurements in women presenting with suspected preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…In prospective observational cohort studies, placental growth factor (PlGF) <5th centile has good test performance in assessing women with suspected pre‐eclampsia for determining need for delivery for pre‐eclampsia within 14 days of testing . We recently reported in the Placental growth factor for the Assessment of hypeRtensive pRegnant wOmen: a stepped wedge Trial (PARROT) that PlGF testing used alongside a clinical management algorithm reduced the time to diagnosis of pre‐eclampsia from 4.1 days (usual care) to 1.9 days (intervention) . Where PlGF was implemented, severe maternal adverse outcomes were reduced from 5.4% (24/447; usual care group) to 3.8% (22/573; intervention group), with no evidence of a difference in gestation at delivery (36.6 versus 36.8 weeks).…”
Section: Introductionmentioning
confidence: 99%